Derivate

  • Materia: Derivate
  • Visto: 4179
  • Data: 03/12/2008
  • Di: Redazione StudentVille.it

$y=sinx/(1+tanx)$

esercizio svolto o teoria

A cura di: Francesco Speciale

Svolgimento:
$y=D((sinx)/(1+tanx))$
$y=((D(sinx))(1+tanx)-(sinx)(D(1+tanx))/(1+tanx)^2)$
$y=((D(sinx))(1+tanx)-(sinx)(D(1)+D(tanx))/(1+tanx)^2)$
$y=cosx(1+sinx/cosx)-(sinx)(1/cos^2x)/(1+sinx/cosx)^2$
$y=cosx((cosx+sinx)/cosx)-sinx/cos^2x/(1+(sin^2x/cos^2x)+2*(sinx/cosx))$
$y=cosx+sinx-(sinx/cos^2x)/((cos^2x+sin^2x+2*(sinx/cosx)/cos^2x)$
$y=((cos^3x+cos^2x*sinx-sinx)/(cos^2x))/((1+2sinx*cosx)/cos^2x)$
$y=((cos^3x+cos^2x*sinx-sinx)/(cos^2x))*(cos^2x/(1+sin2x))$
$y=(cos^3x+cos^2x*sinx-sinx)/(1+sin2x)$
quindi:
$y=(cos^3x+(1-sin^2x)(sinx)-sinx)/(1+sin2x)$
$y=(cos^3x+sinx-sin^3x-sinx)/(1+sin2x)$
$y=(cos^3x-sin^3x)/(1+sin2x)$.